The milling parameters of mechanical parts are optimized by NC machining technology - Wang, Zairu (Frontiers in Mechanical Engineering, 2024)
In the field of mechanical manufacturing, CNC machining technology plays an important role in improving the precision and efficiency of parts processing. However, how to further improve the effect of NC machining by optimizing milling parameters is still a key problem. The aim of this study is to optimize CNC milling parameters through systematic research and experiments to improve the machining efficiency and quality of mechanical parts. By adjusting the key parameters such as tool speed, feed speed and cutting depth, the influence of these parameters on the milling process was studied systematically by using advanced CNC machining equipment. Through the collection and analysis of experimental data, the mathematical model is established, and the optimization algorithm is applied to find the best combination of milling parameters. The experimental results show that under the optimal parameter combination, the surface quality of parts can be improved significantly, the machining time can be reduced, and the tool wear can be reduced.This research successfully realizes the optimization of milling parameters of mechanical parts through CNC machining technology, and provides an effective solution for improving machining efficiency and reducing cost.This not only has guiding significance for the application of CNC machining technology, but also has important promotion value in actual production.